Black necklace from Polish excavations in Novae - Kubczak, Jerzy (Balcanica Posnaniensia. Acta et studia, 1990)
The article discusses the discovery of a black necklace found in a female burial in Novae. The problem concerns the interpretation of the function and meaning of jewelry in cultural and symbolic contexts. The aim of the work is to analyze the material, form, and significance of the ornament. The author applies archaeological and comparative methods. The most important results indicate that the necklace consisted of 156 beads, probably made of jet, and dates to the 3rd–4th century AD, with possible analogies in the Rhine region. The object was attributed magical and protective properties, particularly related to femininity and the life cycle. The conclusion is that the necklace should be interpreted as an object of not only decorative but also symbolic and ritual significance.